2015
DOI: 10.1021/acs.jpcc.5b02096
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Layered Arsenic and Antimony Arsenide

Abstract: Layered materials exhibit intriguing electronic characteristics and the search for new types of two-dimensional (2D) structures is of importance for future device fabrication. Using state-of-art first principle calculations, we identify and characterize the structural and electronic properties of two 2D layered arsenic materials, namely, arsenic and its alloy AsSb. The stable 2D structural configuration of arsenic is confirmed to be the low-buckled two-dimensional hexagonal structure by phonon and binding ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
152
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(166 citation statements)
references
References 32 publications
13
152
0
1
Order By: Relevance
“…They also showed that these structures are stable against the long-wavelength displacements indicating the stability at T = 0 K. The predicted semiconducting character having a band gap in the range of 1.5-2.10 eV and other properties of arsenene have attracted considerable interest. Very recently, various theoretical studies contributed for better understanding of arsenene [10][11][12][13][14][15][16]. Promising progress towards the synthesis of these phases has also been reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that these structures are stable against the long-wavelength displacements indicating the stability at T = 0 K. The predicted semiconducting character having a band gap in the range of 1.5-2.10 eV and other properties of arsenene have attracted considerable interest. Very recently, various theoretical studies contributed for better understanding of arsenene [10][11][12][13][14][15][16]. Promising progress towards the synthesis of these phases has also been reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse allotropes of arsenene have been studied more with a focus on their structural, mechanical, and electronic properties, where arsenene and antimonene were also found to display high carrier mobility, superior mechanical properties, negative Poisson's ratio, and possible topological phase transition features in themselves [19][20][21][22][23][24][25][26][27]. The layered three-dimensional (3D) phase of arsenic, i.e., gray arsenic, presents strong evidence that single-layer arsenic can exist as a local minima in the Born-Oppenheimer surface.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The indirect band gap of its monolayer can also be tuned to a direct band gap under biaxial strain. 14 Herein, we investigate interesting electronic properties of 2D phases of arsenic phosphide under strain. This material differs from pure phosphorene or arsenene in that it can possess more diverse phases depending on the topological arrangement of the two types of atoms.…”
Section: Introductionmentioning
confidence: 99%